Celebrity Endorser, Online Customer Review, Online Customer Rating Terhadap Keputusan Pembelian dengan Kepercayaan Sebagai Variabel Intervening pada Marketplace Tokopedia - Denny Pratama Putra; Lia Suprihartini; Roni Kurniawan (Bahtera Inovasi, 2021)
Broadly speaking, this study aims to determine the effect of Celebrity Endorser, Online Customer Review and Online Customer Rating partially on Purchase Decision, the effect of Celebrity Endorser, Online Customer Review, and Online Customer Rating partially on Trust, the effect of Purchase Decision on Trust, Celebrity Endorser on Purchase Decision through Trust, the effect of Online Customer Review on Purchase Decision through Trust and the influence of Online Customer Rating on Purchase Decision through Trust. The population in this study were all users of Tokopedia who ever purchased at Tokopedia. Determination of the sample using the incidental sampling method, with the sampling technique using the Lameshow' formula to obtain 100 respondents. The data collection method used is a questionnaire. The analytical method used in this research is descriptive test, data quality test, classical assumption test, path analysis and hypothesis testing. The results of the analysis in this study indicate that Celebrity Endorser partially has significant effect on Purchase Decision, partially Online Customer Review has significant effect on Purchase Decision. Online Customer Rating partially has significant effect on Purchase Decision. Partial Trust has a significant effect on Purchase Decision. Trust is not able to mediate between Celebrity Endorser, Online Customer Review and Online Customer Rating on purchase intention. Based on the research results, Tokopedia is expected to continue to increase Purchase Decision by taking into account the factors that support and support Celebrity Endorser, Online Customer Review, and Online Customer Rating.